2007
DOI: 10.1002/art.22375
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated damage accrual among men with systemic lupus erythematosus: XLIV. Results from a multiethnic US cohort

Abstract: Objective. To determine the impact of the patient's sex on the manifestations and outcome of systemic lupus erythematosus (SLE).Methods. We studied SLE patients who were ages 16 years or older and had a disease duration of <5 years at the time of enrollment in the LUpus in MInorities, NAture versus nurture cohort, a multiethnic cohort consisting of Hispanic, African American, and Caucasian patients. Socioeconomic/demographic, clinical, and serologic features, as well as disease activity (by the Systemic Lupus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
132
6
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(171 citation statements)
references
References 25 publications
27
132
6
6
Order By: Relevance
“…Findings of several studies have demonstrated that male SLE patients present a typical manifestation, tend to have a significantly worse prognosis and have more serious kidney involvement (41)(42)(43). More specifically, a recent study has addressed the gender-based differences in Brazilian lupus patients and demonstrated that male patients had more severe LN, as indicated by higher creatinine levels and by comparison of the histopathological activity index values when compared to females diagnosed with this renal abnormality (44).…”
Section: Discussionmentioning
confidence: 99%
“…Findings of several studies have demonstrated that male SLE patients present a typical manifestation, tend to have a significantly worse prognosis and have more serious kidney involvement (41)(42)(43). More specifically, a recent study has addressed the gender-based differences in Brazilian lupus patients and demonstrated that male patients had more severe LN, as indicated by higher creatinine levels and by comparison of the histopathological activity index values when compared to females diagnosed with this renal abnormality (44).…”
Section: Discussionmentioning
confidence: 99%
“…Andrade и соавт. [21] при изучении пациентов мужского и женского пола со средней продолжительностью СКВ, равной 58,9±44,2 (M±SD) и 63,7±42,6 мес соответственно, установили, что более раннее развитие повреждения ассоциировано с мужским полом, возрастом, этнической принадлежностью, употреблением алкоголя, активностью и аномальным поведением, связан-ным с болезнью. В другом исследовании при изучении муж-чин и женщин, больных СКВ, одного возраста, имевших сходные давность, течение заболевания и длительность на-блюдения, установлено, что сумма баллов ИП у мужчин бы-ла достоверно выше, чем у женщин [22].…”
Section: демографические факторыunclassified
“…Активность болезни и выраженность обострения во время проведения исследования также предшествовали нара-станию степени повреждения в гонконгской когорте [32]. Прямая связь между высокой активностью и развитием по-вреждений выявлена и в других исследованиях [21,41].…”
Section: и н д е к с п о в р е ж д е н и я S L I C C ( S Y S T E M I unclassified
“…Two trials are 6. Possible future therapies 6.1 Abatacept Binding of CD28 on T cells to its ligand CD80/86 on APCs and activated B cells provides the major costimulatory activation signal to T cells. Endogenous CTLA-4 is an inhibitory molecule on previously activated T cells that binds CD80/86 with higher affinity than CD28.…”
Section: Ataciceptmentioning
confidence: 99%